Jerusalem in America's Foreign Policy, 1947-1997 - Slonim, Shlomo (International Law - Book Archive pre-2000., 1998)
A comprehensive and innovative examination of US policy on the Jerusalem issue over the past half-century, this study analyzes the complex political and legal factors, both domestic and international, which have shaped executive decisions. The book provides a unique entry into the variations in policy from administration to administration, and the increasingly assertive role of Congress. Based on insights garnered from the past, the author offers useful suggestions for a reality-bound future approach to a problem which is central to resolution of the protracted Arab-Israeli dispute, and thus to security throughout the Middle East.